2022
DOI: 10.1097/md.0000000000029037
|View full text |Cite
|
Sign up to set email alerts
|

Identification of risk factors involved in recurrence after common bile duct stone removal with ERCP

Abstract: Recurrent stone detection is common after endoscopic treatment of common bile duct stones (CBDS). This study aimed to identify the risk factors for recurrence of CBDS.We retrospectively evaluated 14 patients who underwent endoscopic treatment for CBDS. Risk factors for single and multiple recurrent CBDSs were evaluated using logistic regression analysis.Endoscopic and needle-knife precut sphincterotomy was performed in 506 and 112 patients, respectively. There was 1 recurrence in 85 patients (13.8%), 2 recurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 21 publications
0
10
2
Order By: Relevance
“…Overall, 35 studies ( n = 11,771) reported the recurrence of CBD stones after initial clearance with ERCP 1–6,11–27,29–41 . The pooled event rate for the recurrence of CBD stones was 12.6% (95% confidence interval [CI]: 11.2–13.9; I 2 = 79.2%).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, 35 studies ( n = 11,771) reported the recurrence of CBD stones after initial clearance with ERCP 1–6,11–27,29–41 . The pooled event rate for the recurrence of CBD stones was 12.6% (95% confidence interval [CI]: 11.2–13.9; I 2 = 79.2%).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows the PRISMA diagram for the study selection and inclusion process. A total of 37 studies with 12,952 patients were included in the final analysis 1–6,11–41 . Table 1 shows the baseline characteristics of the studies included in the present meta‐analysis, along with the study quality assessment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations